Alteration in Expression of miR-32 and FBXW7 Tumor Suppressor in Plasma Samples of Patients with T-cell Acute Lymphoblastic Leukemia - Mansouri S; Khansarinejad B; Mosayebi G; Eghbali A; Mondanizadeh M (Cancer Management and Research, 2020)
Sanaz Mansouri,1,* Behzad Khansarinejad,2,* Ghasem Mosayebi,2 Aziz Eghbali,3 Mahdieh Mondanizadeh1,4 1Department of Biotechnology and Molecular Medicine, Arak University of Medical Sciences, Arak, Iran; 2Department of Microbiology and Immunology, Arak University of Medical Sciences, Arak, Iran; 3Department of Pediatrics, School of Medicine, Arak University of Medical Sciences, Arak, Iran; 4Molecular and Medicine Research Center, Arak University of Medical Sciences, Arak, Iran*These authors contributed equally to this workCorrespondence: Mahdieh MondanizadehDepartment of Biotechnology and Molecular Medicine, Arak University of Medical Sciences, Arak, IranTel/Fax +98-8634173526Email m_mondanizadeh@yahoo.comBackground: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive and malignant neoplasm that arises from the hematopoietic T-cell precursors. Inactivation of FBXW7 gene is frequently observed in T-cell acute lymphoblastic leukemia, suggesting a significant tumor-suppressive role for FBXW7 in the pathobiology of this leukemia. Considering the role of microRNAs in cell proliferation and regulation of apoptosis, the aim of this study was to identify novel oncogenic microRNAs that suppress FBXW7 in patients with T-ALL.Patients and Methods: The expression levels of two bioinformatically predicted microRNAs – miR-32 and miR-107 were compared in patients with T-ALL and a control group. A total of 80 plasma samples were subjected to RNA extraction, and the microRNA expression profiles were assessed by the RT-qPCR. The expression level of miR-103 was used as the endogenous reference for normalization of quantitative data.Results: The plasma levels of miR-32 and miR-107 in patients with T-ALL were significantly higher (5.65, P < 0.001) and lower (0.432, P = 0.002), respectively. On the other hand, the expression levels of FBXW7 gene were significantly downregulated by – 76.9 fold in T-ALL patients (P < 0.001). The results of the ROC curve analysis indicated that overexpression of miR-32 might be used to distinguish T-ALL patients with reasonable sensitivity and specificity.Conclusion: miR-32 is considered as a novel oncomir that targets FBXW7 and might have a role in the etiology or progression of T-ALL. Furthermore, miR-32 can potentially serve as a non-invasive biomarker for detection of T-ALL.Keywords: biomarker, FBXW7, T-ALL, microRNA